NATURAL AND SYNTHETIC ANTIMICROBIALS AGENT FOR TEXTILE: A REVIEW - Try Purwanti; Nissa Nurfajrin Solihat; Widya Fatriasari; Deded Sarip Nawaw (Jurnal Industri Hasil Perkebunan, 2021)
Raising public health awareness of personal hygiene, particularly in the context of the Covid-19 situation, has increased the research on antimicrobial textiles, not only for medical devices but also for daily wear. Textiles, particularly natural-based fibers, have a large surface area that can retain moisture for microorganism growth, resulting in a pathogenic effect on the user. As a result of the high demand for natural-based textiles, various approaches to applying antimicrobial agents to natural fabrics have been investigated. Any antimicrobial treatments used in textiles must be human-safe, effective against pathogenic microbial, and resistant to non-pathogenic microbial in skin. Antimicrobial agents are classified into two types: natural and synthetic. Both types have certain advantage and disadvantage, but they have the same crucial parameters such as antimicrobial agent concentration, bacterium species, and finishing procedures to improve durability and efficacy. This paper discusses the use of natural and synthetic antimicrobial agents on natural fiber, with natural antimicrobials including lignin, chitosan, and tannin, and synthetic antimicrobials including metal, organic, and inorganic compounds. The application method of them on fabrics is also presented.